Snow White - Sugimoto, Hiroshi 1948- (Damiani, 2017)
All of the photographs in 'Snow White' are from his Theaters series and include many of his well known photographs of classic movie palaces and drive-ins, along with new photographs of Italian opera houses and abandoned theaters. Sugimoto began the Theaters series four decades ago. To make these images, he exposes the film inside the dark theater (or in the case of the drive-ins, outside at night) for the duration of the movie. The running movie is the only source of light bringing out the architectural details of these spaces. The Disney movie 'Snow White' was running when Sugimoto photographed 'Palace Theater, Gary', 2013, one of the abandoned theaters that is reproduced here. In this book, Sugimoto reveals for the first time the movies that were screened when he took these photographs and the exposure time of each photograph
In Aluminium-Schuber
400 Exemplare, nummeriert und signiert
Keywords: Sugimoto, Hiroshi -- 1948-; Bildband